A saúde dos cuidadores de idosos com diagnóstico indicativo de Alzheimer - Nierotka, Rosane Paula (2014)
Objective: To analyze the health of caregivers of patients with Alzheimer's diagnosis indicative factors. Methodology: This is a quantitative study of cross- cutting and descriptive. The study population was intentionally set by caregivers of both genders enrolled in stock research "functional capacity in elderly indicative diagnosis of Alzheimer Chapecó" belonging to the group Human Aging and Disorders of Movement Unochapecó, totaling 41 caregivers. The data collection instruments used were a questionnaire adapted Profile Questionnaire Family Caregiving - PFD, in case of existence of Brief Pain Inventory Pain BPI - (Brief Pain Inventory) and the Zarit Burden Scale Interview - ZBI. Data were organized in a database in Excel Calc spreadsheet and analyzed through a descriptive analysis, establishing mean, standard deviation and frequency application by Statistical Package for Social Sciences for Windows (SPSS). Results: The result was compelled in one text annexed to this scientific output. This production is titled "Health perception and pain intensity associated with the time to care for the elderly with Alzheimer's", aimed to analyze the health perception and pain intensity associated with the time to care for the elderly with Alzheimer's. It was found that longer dedicated to the care seems to interfere with the perception of health of caregivers for the past five years and compared with others of the same age. However the advancement in time devoted to care, does not interfere in the intensity of pain experienced by the caregiver. It is observed that the group of caregivers who have no pain or only mild reports a perception of better health. Conclusion: The study had limitations in the sample of caregivers. Results highlight the need for greater attention to the caregiver of the elderly and further studies in these contexts